Pengaruh Penggunaan Aplikasi Google Play Books Terhadap Tingkat Pemahaman Belajar Siswa pada Mata Pelajaran Informatika di SMK Al-Ihya Selajambe - Fahri, Amar; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the effect of using the Google Play Books application on students' learning comprehension levels in Informatics at SMK Al-Ihya Selajambe. The background of this study stems from the need for innovative digital learning media that can increase student engagement and deepen their understanding of the material. This study uses a quantitative experimental method with a pretest-posttest control group design. The research population consisted of all 10th grade students, with a purposive sample of two classes, each consisting of 32 students, namely the experimental class and the control class. The research instrument was a validated learning comprehension test, while data were collected through pretest and posttest administration and then analyzed using an independent t-test with a significance level of 0.05. The results showed that the average posttest score in the experimental class (90.75) was higher than that in the control class (85.06). The hypothesis test produced a significance value of <0.001, indicating a significant difference between the two groups. Thus, the use of Google Play Books was proven to have a positive and significant effect on improving students' learning comprehension.